Utilization of the e-Polvot System to Increase Student Participation in Higher Education - Anam, M. Khairul; Zoromi, Fransiskus; Hamdani, Hamdani; Efendi, Yoyon; Kudadiri, Parlindungan (JTERA (Jurnal Teknologi Rekayasa), 2025)
STMIK Amik Riau currently has a student organization, one of which is the Student Executive Board (BEM). Every year, BEM is chosen as the representative of the students to voice their aspirations both within and outside the campus. The election process for BEM representatives is still conducted traditionally on campus. However, not all students can participate in the election process regularly, resulting in some students being unable to vote for the candidates for the student president and vice-president. To address this issue, a system is needed to facilitate the election process. One solution is to conduct electronic elections, allowing all students to vote from anywhere using the internet. In this research, the developed system is called e-Polvot (Electronic Polling and Voting). This system can be used by anyone to conduct elections by creating their own election campaigns. Before designing the system, the research conducted a measurement of the potential users using the TRI model. The results from the TRI measurement were then used to determine whether the system should be developed or not. Subsequently, the e-Polvot system was built and implemented at STMIK Amik Riau. After the implementation, the system underwent black box testing to ensure its functionality. The testing results showed that the main features of the e-Polvot system were able to perform well.